2017
DOI: 10.1155/2017/5957076
|View full text |Cite
|
Sign up to set email alerts
|

Central Sensitization-Based Classification for Temporomandibular Disorders: A Pathogenetic Hypothesis

Abstract: Dysregulation of Autonomic Nervous System (ANS) and central pain pathways in temporomandibular disorders (TMD) is a growing evidence. Authors include some forms of TMD among central sensitization syndromes (CSS), a group of pathologies characterized by central morphofunctional alterations. Central Sensitization Inventory (CSI) is useful for clinical diagnosis. Clinical examination and CSI cannot identify the central site(s) affected in these diseases. Ultralow frequency transcutaneous electrical nerve stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 137 publications
(123 reference statements)
2
38
1
Order By: Relevance
“…ese results are consistent with accumulating evidence that indicates that subjects suffering from TMD exhibit dysregulation of the systems that control the response of the autonomous and somatomotor systems to sensory stimuli [36]. Furthermore, it has been hypothesized that this dysregulation in TMD patients represents a form of CS [37][38][39][40][41]. In fact, our CSI data indicate that TMD subjects receive high scores, and this is consistent with a role for central involvement that is not observed in control subjects.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…ese results are consistent with accumulating evidence that indicates that subjects suffering from TMD exhibit dysregulation of the systems that control the response of the autonomous and somatomotor systems to sensory stimuli [36]. Furthermore, it has been hypothesized that this dysregulation in TMD patients represents a form of CS [37][38][39][40][41]. In fact, our CSI data indicate that TMD subjects receive high scores, and this is consistent with a role for central involvement that is not observed in control subjects.…”
Section: Discussionsupporting
confidence: 91%
“…In fact, our CSI data indicate that TMD subjects receive high scores, and this is consistent with a role for central involvement that is not observed in control subjects. In previous studies of central dysregulation in TMD, a notable observation is that the pupil system of TMD subjects responds in a dysregulated manner to teeth clenching in response to administration of ultra-low-frequency transcutaneous electrical nervous stimulation (ULF-TENS) with sensory amplitude, which represents a central action mechanism [27,37,[42][43][44]. In the present study, opening of the eyes was found to have a significant effect on EMG values only when TMD subjects opened their eyes while wearing glasses that provided standard eye correction.…”
Section: Discussionmentioning
confidence: 99%
“…A separate study with the French CSI found even better sensitivity (95%) and specificity (90%) with distinguishing between fibromyalgia subjects and acute ankle pain and control subjects. This 40‐point cut‐off score has been recommended as one component of an algorithm for helping to identify CS‐related pain (vs. neuropathic and nociceptive pain) in generalized chronic pain (Nijs, Malfliet, Ickmans, Baert, & Meeus, ; Nijs, Torres‐Cueco et al., ) and low back pain subjects (Nijs, Apeldoorn et al., ), and for classifying of temporomandibular joint disorder subtypes (Monaco, Cattaneo, Marci, Pietropaoli, & Ortu, ). Most recently, five severity levels have been developed to help aid in the clinical interpretation of the CSI (subclinical = 0–29; mild = 30–39; moderate = 40–49; severe = 50–59; and extreme = 60–100) (Neblett, Hartzell, Mayer, Cohen, & Gatchel, ).…”
Section: Interpreting Csi Scoresmentioning
confidence: 99%
“…The aetiology of TMD is multifactorial in nature, with risk factors thought to range from; individual genetic and sex-based (more common in females) factors, dental related causes including occlusion issues and bruxism, to stress, depression and anxiety related states [5]. There has been evidence to suggest that patients who have experienced TMD, may also present with functional and structural changes in the thalamus, somatosensory cortex and some have dysfunction in the pain inhibition systems [6]. Of those patients who present with chronic pain initiated by TMD, some have an increase in generalised pain sensitivity, which can be characteristic of central sensitisation of the nervous system [7].…”
Section: Introductionmentioning
confidence: 99%